Immune‐related adverse events of a PD‐L1 inhibitor plus chemotherapy versus a PD‐L1 inhibitor alone in first‐line treatment for advanced non–small cell lung cancer: A meta‐analysis of randomized control trials. Issue 5 (29th October 2020) - Wang, Manting; Liang, Hengrui; Wang, Wei; Zhao, Shen; Cai, Xiuyu; Zhao, Yi; Li, Caichen; Cheng, Bo; Xiong, Shan; Li, Jianfu; He, Jianxing; Liang, Wenhua
Abstract : Background: The addition of chemotherapy to a programmed death 1/programmed death ligand 1 (PD‐L1) inhibitor is a more effective option as a first‐line treatment for advanced non–small cell lung cancer (NSCLC). It might also inhibit an overactive immune response and thereby reduce immune‐related adverse events (irAEs). This meta‐analysis assessed the rate of irAEs with a PD‐(L)1 inhibitor plus chemotherapy (I+C) versus a PD‐(L)1 inhibitor alone (I) and evaluated the indirect relative risk (RR) of I+C versus I. Methods: The protocol of this study was registered with PROSPERO (CRD42020139923). The pooled rates of irAEs at different grades were calculated by a single‐arm meta‐analysis weighted by sample size, and RRs were determined by direct meta‐analysis and indirect treatment comparison. Results: Overall, I+C had a lower rate of grade 3 or higher irAEs than I (7.1% vs 10.6%; indirect RR, 0.516; 95% confidence interval [CI], 0.291‐0.916), although irAEs of any grade were similar. The rate of pneumonitis with I+C was lower than the rate with I for any grade (5.9% vs 7.1%; indirect RR, 0.217; 95% CI, 0.080‐0.588) and for grade 3 or higher. In the endocrine system, I+C was associated with a lower overall ratein comparison with I (16.1% vs 20.1%; indirect RR, 0.260; 95% CI, 0.120‐0.564), whereas irAEs of the digestive system were similar with I+C and I. In other systems, I+C decreased the rate of skin reactions, including rash, in comparison with I (10.4% vs 12.9%; indirect RR, 0.474; 95% CI, 0.299‐0.751). The rate of grade 3 or higher skin reactions (excluding rash) also decreased with I+C versus I (1.1% vs 2.0%) with an indirect RR of 0.158 (95% CI, 0.032‐0.765), whereas other included irAEs were similar. Conclusions: In comparison with a PD‐(L)1 inhibitor alone, a combination with chemotherapy for the first‐line treatment of NSCLC decreased the rates of most irAEs, such as pneumonitis and endocrine and skin reactions, and the overall rate. Lay Summary: In the first‐line treatment of advanced non–small cell lung cancer (NSCLC), the addition of chemotherapy to a programmed death 1/programmed death ligand 1 (PD‐(L)1) inhibitor is a more effective option. Adding chemotherapy might reduce immune‐related adverse events (irAEs). Thus, this article assesses the rate of irAEs with a PD‐(L)1 inhibitor plus chemotherapy (I+C) in comparison with a PD‐(L)1 inhibitor alone (I) and evaluates the indirect relative risk (RR) with I+C versus I. The key finding is that in comparison with a PD‐(L)1 inhibitor alone, a combination with chemotherapy for the first‐line treatment of NSCLC decreases the rates of most irAEs, such as pneumonitis and endocrine and skin reactions, and the overall rate. Abstract : The combination of a programmed death‐ligand 1 (PD‐L1) inhibitor and chemotherapy decreases the rates of most immune‐related adverse events in comparison with just a PD‐L1 inhibitor in the first‐line treatment of non–small cell lung cancer, such as pneumonitis and endocrine and skin reactions, and the overall rate.